Is there a link between the autonomy of women and maternal healthcare utilization in Nigeria? A cross-sectional survey - Emmanuel Kolawole Odusina; Oluwarotimi Samuel Oladele (BMC, 2023)
Abstract Background Despite legislation and intervention programmes, the rates of maternal and child mortality in Nigeria remain high. Sustainable development goals on mother and child mortality would be a mirage if this continues. The study investigated the autonomy of women (women's decision-making autonomy) and the use of maternal health-care services in Nigeria. Methods Secondary data obtained from the Nigeria Demographic and Health Survey, 2018 were used in this investigation. Women who indicated they gave birth in the five-year before the surveys were considered in the study. The association between autonomy of women and maternal health-care utilization was studied using binary logistic regression models. Results In total, about one-fifth of the women (19.6%) indicated they had at least eight ANC visits for their most recent birth. Overall, 40.5% of the women gave birth in a health institution, and 20.1% went for postnatal checkups. The use of health-care services was significantly related to the autonomy of women. Women's and husbands/partners' educational levels, residency and ethnicity were socio-demographic characteristics that influenced women's healthcare service consumption. Conclusions For most recent childbirth, most women did not utilise the health-care services in Nigeria. To enhance the autonomy of women and, as a result, maternal health-care services use in Nigeria, effective interventions, policies, and programmes are required.